A Real-World Study Using Claims Data to Evaluate Possible Failure of Opioid Treatment Regimens Among Patients with Hip and/or Knee Osteoarthritis in the US - Gandhi K; Wei W; Huang A; Wang L; Iyer R; Katz NP (Dove Medical Press, 2020)
Kavita Gandhi,1 Wenhui Wei,2 Ahong Huang,3 Li Wang,3 Ravi Iyer,1 Nathaniel P Katz4,5 1Teva Pharmaceutical Industries, Frazer, PA, USA; 2Regeneron Pharmaceuticals, Tarrytown, NY, USA; 3STATinMED Research, Dallas, TX, USA; 4Analgesic Solutions, Wayland, MA, USA; 5Tufts University School of Medicine, Boston, MA, USACorrespondence: Nathaniel P KatzAnalgesic Solutions, 321 Commonwealth Road, Ste 204, Wayland, MA 01778, USATel +1 781 444-9605Fax +1 973 553-8888Email nkatz@analgesicsolutions.comBackground: Although opioids may be used in the management of pain in patients with osteoarthritis (OA), there is a dearth of real-world data characterizing opioid regimen failure in these patients.Objective: Using claims data, this study explored measures that may be potentially indicative of opioid treatment failure and the association of such potential failure with health care resource utilization (HRU) and costs.Patients and Methods: Using a national employer-sponsored insurance claims database covering the years 2011– 2016, this retrospective longitudinal study identified adults with hip/knee osteoarthritis who filled ≥ 1 opioid prescription (index event) and had continuous health plan enrollment 6 months pre- and ≥ 12 months post-index. Index opioid regimen intensity was defined in the 3-month post-index period by frequency, average daily dose, and duration of action. Possible index opioid regimen failure was defined as an increase in opioid regimen intensity, addition of a non-opioid pain medication, joint surgery, or opioid-abuse-related events. One-year follow-up HRU and costs were compared between those with possible treatment failure and those without.Results: Among 271,512 OA patients (61.5% knee; 11.1% hip; 27.4% both), 34.9% met the definition of possible index opioid regimen failure within a year: increased regimen intensity (16.1%), joint surgery (14.0%), addition of non-opioid pain medication (11.4%), and opioid-abuse-related events (1.9%). Rates of possible failure generally increased with higher index regimen intensity. Compared with those who did not fail, those who potentially failed their index treatment regimen had significantly higher HRU (P< 0.001), and all-cause ($36,699 vs $15,114) and osteoarthritis-related costs ($17,298 vs $1,967) (both P< 0.0001).Conclusion: Among OA patients treated with opioids, approximately one-third may fail their index opioid regimen within a year and incur significantly higher HRU and costs than those without. Further research is needed to validate these findings with clinical outcomes.Keywords: osteoarthritis, pain, opioids, treatment failure, health care resource use, costs